Pharmacologic ascorbate synergizes with gemcitabine in preclinical models of pancreatic cancer - Espey, Michael Graham (2011)
Conventional treatment approaches have had little impact on the course of pancreatic cancer, which has the highest fatality rate among cancers. Gemcitabine, the primary therapeutic agent for pancreatic carcinoma, produces minimal survival benefit as a single agent. Therefore, numerous efforts have focused on gemcitabine combination treatments. Using a ratio design, this study established that combining pharmacologically achievable concentrations of ascorbate with gemcitabine resulted in a synergistic cytotoxic response in eight pancreatic tumor cell lines. Sensitization was evident regardless of inherent gemcitabine resistance and epithelial–mesenchymal phenotype. Our analysis suggested that the promiscuous oxidative actions of H(2)O(2) derived from pharmacologic ascorbate can culminate in synergism independent of the cancer cell's underlying phenotype and resistance to gemcitabine monotherapy. Gemcitabine–ascorbate combinations administered to mice bearing pancreatic tumor xenografts consistently enhanced inhibition of growth compared to gemcitabine alone, produced 50% growth inhibition in a tumor type not responsive to gemcitabine, and demonstrated a gemcitabine dose-sparing effect. These data support the testing of pharmacologic ascorbate in adjunctive treatments for cancers prone to high failure rates with conventional therapeutic regimens, such as pancreatic cancer.